A model of West African millet prices in rural markets. (April 2015) - Higgins, Nathaniel; Hintermann, Beat; Brown, Molly E.
Highlights: We build a spatially-explicit price forecasting model for millet in West Africa. We obtain local price forecasts at a fine scale using prices in nearby markets. Including satellite-derived information (NDVI) improves price forecasts. Our model can be used in early warning of food insecurity. Abstract: In this article we specify a model of millet prices in the three West African countries of Burkina Faso, Mali, and Niger. Using data obtained from USAID's Famine Early Warning Systems Network (FEWS NET) we present a unique regional millet price forecasting model that takes advantage of the panel nature of our data and accounts for the distance of rural markets from capital cities. Another novel aspect of our analysis is our use of the Normalized Difference Vegetation Index (NDVI) to detect and control for variation in conditions for productivity. We find that including NDVI information significantly improves price forecasts.